The impact of FSC certification perceived by employees of brazilian companies - Nunes, Moema Pereira; Weber, Bruna Rafaela Kercher; Fagundes, Camila; Schreiber, Dusan (Revista de Administração da UFSM, 2024)
Purpose: This study evaluates empirical evidence on the perceptions of employees on the positive and negative impacts of Forest Stewarship Council (FSC) certification on Brazilian companies. Methodology: A survey was developed, and data from 149 employees of certified companies was collected. A scale of positive and negative impacts based on the literature was developed. The Jonckheere-Terpstra test was used to compare the statistical differences between the attributes under analysis. An exploratory factor analysis was also developed with a quantitative approach. Results: The most positive perceptions are related to the protection of the forest and society. Regarding the negative aspects, the misinformation about the certifications and the cost to carry out the certification were highlighted. Originality: The existing literature about FSC certification focuses on company managers and/or external stakeholders. A study on the perspective of employees from certified companies is important to ensure the well-being of employees, promote sustainability and corporate social responsibility, identify areas for improvement, and strengthen the company’s reputation and credibility in the market.